2008
DOI: 10.1111/j.1574-6968.2008.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Importation of the major pilin TcpA gene and frequent recombination drive the divergence of theVibriopathogenicity island inVibrio cholerae

Abstract: The Vibrio pathogenicity island (VPI) encodes the toxin-coregulated pilus and other virulence factors for Vibrio cholerae to colonize the human intestine to cause cholera. We assessed the level of genetic variation of VPI in nine nonpandemic isolates, and compared them with the sixth and seventh pandemic strains by sequencing c. 5 kb each from the start, middle and end regions of the VPI. Variation is similar among the three regions at around 2%, except for the tcpA gene, which has a much higher level of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The findings reported here are supported by those of Karaolis et al (2001) who demonstrated that the central region of the VPI of tcpA contains most of the divergence between the VPIs of the 6th (classic) and the 7th (El Tor) pandemic strains. Previous studies by others have described that the genetic variants of the TCP island were carried by a number of environmental V. cholerae strains belonging to non-epidemic serogroups (Boyd & Waldor, 2002;Mukhopadhyay et al, 2001;Tay et al, 2008). Overall, the consensus all published reports have indicates mutational events in the tcp region.…”
Section: Ljf-vpir Aldaf-tagar Vpi2f-r Vpi3f-r Vpi4f-r Vpi5f-r Tcpif-qmentioning
confidence: 56%
“…The findings reported here are supported by those of Karaolis et al (2001) who demonstrated that the central region of the VPI of tcpA contains most of the divergence between the VPIs of the 6th (classic) and the 7th (El Tor) pandemic strains. Previous studies by others have described that the genetic variants of the TCP island were carried by a number of environmental V. cholerae strains belonging to non-epidemic serogroups (Boyd & Waldor, 2002;Mukhopadhyay et al, 2001;Tay et al, 2008). Overall, the consensus all published reports have indicates mutational events in the tcp region.…”
Section: Ljf-vpir Aldaf-tagar Vpi2f-r Vpi3f-r Vpi4f-r Vpi5f-r Tcpif-qmentioning
confidence: 56%
“…PCR assays (Table 2) were used for the detection of the ctxAB [39], tcpA [40], zot [41], NAG-ST [16], T3SS ( vcsC2 and vcsV2 ) [16,28], ompW [42], toxR [42] and hlyA genes [43]. All isolates were positive for V. cholerae specific gene ompW by PCR, but were negative for ctxAB , zot , tcpA and NAG-ST. All isolates were positive for toxR (Table 1), except for N743 which was toxR negative.…”
Section: Resultsmentioning
confidence: 99%
“…The O1 serogroup contains the genetically similar classical and El Tor biotypes, which vary at only a few loci, including that for the major pilin subunit, TcpA (387). Comparison of TcpA sequences between those two serogroups showed that they were ϳ80% identical, with the N terminus being the most highly conserved region.…”
Section: Diversity Among T4b Pilinsmentioning
confidence: 99%
“…Comparison of TcpA sequences between those two serogroups showed that they were ϳ80% identical, with the N terminus being the most highly conserved region. The primary mechanism responsible for generating TcpA diversity was proposed to be recombination rather than mutation (387). Even small sequence changes in TcpA have profound effects on pilus function, as single point mutations in the D region caused a loss of pilus bundling, a phenotype important to pathogenesis.…”
Section: Diversity Among T4b Pilinsmentioning
confidence: 99%